2015
DOI: 10.1002/geot.201500033
|View full text |Cite
|
Sign up to set email alerts
|

The Granitztal tunnel chain / Tunnelkette Granitztal

Abstract: The Granitztal tunnel chain, located after the Koralm Tunnel in a southward direction and adjoining the new IC station in the Lavanttal,, essentially consists of the Deutsch Grutschen and Langer Berg Tunnels, which are being excavated cyclically, and the Granitztal gallery in cut-and-cover. The article offers a general overview of the project, described the geological and geotechnical conditions and compares the experience gained in the current early construction phase with the underlying conditions for design… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2016
2016
2018
2018

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 1 publication
0
3
0
1
Order By: Relevance
“…The groundwater conditions are documented as dry to mountain damp. A detailed description of the geological-geotechnical conditions can be found in [1] [2].…”
Section: Geological and Geotechnical Conditions 21 Deutsch Grutschenmentioning
confidence: 99%
See 1 more Smart Citation
“…The groundwater conditions are documented as dry to mountain damp. A detailed description of the geological-geotechnical conditions can be found in [1] [2].…”
Section: Geological and Geotechnical Conditions 21 Deutsch Grutschenmentioning
confidence: 99%
“…Die Bergwasserverhältnisse sind als trocken bis bergfeucht dokumentiert. Eine ausführliche Darstellung der geologisch-geotechnischen Verhältnisse ist in [1] [2] dargelegt. The spatial extent of the anhydrite section was limited to a length of tunnel of about 90 m. In the next 70 m of tunnel, some minimal traces of anhydrite were documented in the rock (cf.…”
Section: Langer Berg Tunnelunclassified
“…An extensive description of the geological/geotechnical situation in the Langer Berg starting cut has already been published in [1]. This article will concentrate on the construction sequence and technology.…”
Section: Intermediate Starting Point In the Granitztalmentioning
confidence: 99%
“…Eine ausführliche Darstellung der geologisch/geotechnischen Situation im Voreinschnitt Langer Berg wurde bereits in [1] The tipping and later removal of the intermediate stockpile was only possible after the stillwater sediments had been mixed in a ratio of 4:1 with the limited amount of material available from the Granitztaler beds. In parallel to the deposition trials, it was found that cutting in about 20 kg/m 3 of lime with a soil stabiliser could achieve similar results.…”
Section: Zwischenangriff Granitztalmentioning
confidence: 99%